PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN PENDERITA HIPERTENSI TENTANG RISIKO STROKE DI DESA MOSSO KABUPATEN MALUKU TENGAH MALUKU - Usman Barus Ohorella; Feby Adolf Metekohy; Irhamdi Achmad (Pusat Penelitian dan Pengabdian Kepada Masyarakat Poltekkes Kemenkes Maluku, 2021)
Background: Stroke is an acute nerve function disorder caused by circulatory disorders on brain, symptoms according to the focal area of brain that is experiencing disorder. The prevalence of stroke increases with increasing in age. Stroke in male groups as high as female groups. The increasing number of people with cardiovascular disease and coronary heart disease (CHD) every year was due to lack of public knowledge about risk factors of heart disease and lack of efforts to prevent the disease. Prevention must be tried as far as possible by controlling the risk factors for cardiovascular disease and CHD. Objective: to determine the effect of health education on the level of knowledge of hypertensive patients about stroke risk in Mosso Village, Maluku. Method: This study used a Quasi experimental design with a pretest posttest with control group design approach. In this design there are two groups, control group and intervention group, with the Probability sampling (simple random sampling with a sample of 47 people with Hypertension patients for each group. Data was collected using questionnaire. Result: The results was statistically analysis with SPSS (paired t test and pooled t test) and showed a significantly differences in the average level of knowledge after the health education intervention in control group (mean diff. -6,936) and intervention group (mean diff. -6,574) (p <0,0001). Conclusion: It was concluded that health education was an effective method in increasing the level of knowledge of hypertension patient about the risk of stroke in Mosso village, Maluku Keyword: Stroke; Hypertension; Knowledge.